Analisis Perbandingan Kinerja Keuangan Perusahaan Badan Usaha Milik Negara (BUMN) Tbk Tahun Fiskal 2025: Pendekatan Analisis Rasio Keuangan dan Composite Scoring - Rizki SyahPutra; Bintang Arbiawan Pangestu; Hermawan Putra; Adinda Mulya Rahma; Shallu Qawsaini; Herayati Herayati (MES Management Journal, 2026)
This study aims to analyze and compare the financial performance of 15 State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the fiscal year 2025. The research employs a quantitative approach with a descriptive-comparative design by examining 13 financial ratios representing four key dimensions: liquidity, solvency, profitability, and activity. These ratios were subsequently integrated using a composite scoring method to provide a more comprehensive assessment of corporate performance. The findings reveal substantial differences in financial performance across sectors. Mining and energy companies demonstrated the strongest financial conditions, characterized by solid liquidity, profitability, and solvency indicators. PT Aneka Tambang Tbk (ANTM) achieved the highest ranking with a composite score of 8.89, followed by PT Timah Tbk (TINS) and PT Pertamina Geothermal Energy Tbk (PGEO). In contrast, construction-sector SOEs experienced significant financial distress, reflected in high leverage, weak liquidity positions, and negative profitability among several companies, including WIKA, WSKT, and ADHI. The study confirms that the composite scoring approach provides a more holistic evaluation than relying on individual financial ratios alone, making it a valuable tool for governments, investors, and corporate management in strategic decision-making processes.